Collaboration and Employee Performance: The Mediating Role of Innovation among Public Sector Employees in East Kalimantan (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study examines the impact of collaboration on employee performance, with innovation as a mediating variable among public sector employees in East Kalimantan, Indonesia. This study employs a quantitative methodology involving 172 respondents from various government institutions. Data analysis was conducted using Partial Least Squares structural equation modeling (PLS-SEM) via SmartPLS 4. The findings indicate that collaboration exerts a positive and significant influence on employee performance both directly and indirectly through innovation. Moreover, innovation plays a crucial mediating role, suggesting that collaborative work environments promote creative problem-solving and knowledge exchange, ultimately enhancing individual performance. These results contribute to the integration of Social Exchange Theory, Knowledge-Based View, and Dynamic Capability Theory in elucidating performance improvement within the public sector. Practically, this study highlights the importance of fostering collaborative cultures and innovation-driven management practices to improve bureaucratic efficiency and public service delivery in developing regions.